Perluasan Kesempatan Kerja bagi Freshgraduate di Masa Pandemi Covid-19, Apa Peran Pemerintah? - Maria Lusyana Br Ginting (Jurnal Ketenagakerjaan, 2021)
The pandemic caused a setback in the field of employment, namely higher unemployment. Data from the Indonesian Chamber of Commerce and Industry as of June 2020 shows that 6 million workers have been laid off. New graduates as young people are experiencing quite the impact of this Covid-19 pandemic. Based on BPS data in August 2020, the TPT for the young age group (15–24 years) is the highest, reaching 20.46 per cent. From these problems, this paper was made. The method used in this paper is a literature review, both from books, journals, newspapers, existing research results, and credible online media. The purpose of this study is to find out how the government's role is in providing expansion of job opportunities for fresh graduates during the COVID-19 pandemic. The results obtained from this study are that the government's role in expanding job opportunities has not been optimally focused on fresh graduates, as seen from several programs that have been issued during the pandemic. The recommendation given is to provide and expand space and access for fresh graduates to be able to develop hard skills and soft skills through verified training that companies have recognized, by adding a focus on expanding job opportunities for fresh graduates by taking into account the needs, interests, talents, and skills of fresh graduates by cooperating collaborating with various universities. Strengthening collaboration and cooperation between the central government, local governments and companies such as BUMN, BUMD, and private.